2008
DOI: 10.2981/0909-6396(2008)14[358:eofmut]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four methods used to estimate population density of moose Alces alces

Abstract: Various survey methods are used to monitor and manage ungulate populations. The choice of optimal method depends on estimation accuracy, management objective and financial constraints. Here we compare estimates produced by four different methods for estimating population size, i.e. aerial counts, hunter observations, pellet group counts and cohort analysis. A Swedish moose Alces alces population was studied during 1973-2005 in the Grimso¨Wildlife Research Area (135 km 2 ). The highest correlation was found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 29 publications
2
74
1
Order By: Relevance
“…As for comparison between areas, HD was a fairly good reflector of the variation in moose density, while SPUE and SMD failed to represent the spatial variation in moose density. However, both observation indices provided a good representation of the temporal variation in moose density within study sites, consistent with previous studies (Ericsson and Wallin 1999, Rö nnegå rd et al 2008. Part of the spatial variation in SPUE was explained by the proportion of deciduous forests, which we believe can have a strong effect on the visual transparency of the forest and thus the probability of detecting a moose.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As for comparison between areas, HD was a fairly good reflector of the variation in moose density, while SPUE and SMD failed to represent the spatial variation in moose density. However, both observation indices provided a good representation of the temporal variation in moose density within study sites, consistent with previous studies (Ericsson and Wallin 1999, Rö nnegå rd et al 2008. Part of the spatial variation in SPUE was explained by the proportion of deciduous forests, which we believe can have a strong effect on the visual transparency of the forest and thus the probability of detecting a moose.…”
Section: Discussionsupporting
confidence: 89%
“…However, as the population abundance is seldom known, an alternative is to compare them with other independent indices or estimates of density (e.g., Skalski et al 2007). For instance, by examining the relationship between the moose, Alces alces, seen per unit effort (SPUE) and moose abundance reconstructed by cohort analysis, concluded that the SPUE may be used for monitoring the temporal variation in moose abundance (see also Rö nnegå rd et al 2008). For many indices, however, the relationship to abundance is at best based on a few studies and comparative merits of indices are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To get an idea of how well harvest density relates to moose density, and with what time lag, we used a subset of years (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) for which we also possessed data on moose seen per hunter-day. This index is based on a large number of moose observations recorded by moose hunters each year and is found to correlate closely with moose density (Ericsson and Wallin 1999, Sylven 2000, Solberg et al 2006, Ronnegard et al 2008. The correlation between moose seen per hunter-day and harvest density in the same year was on average positive (mean r ¼ 0.52, range: À0.61-0.90), indicating that harvest density was quite well tracking the variation in moose density within county.…”
Section: Moose Densitymentioning
confidence: 97%
“…Månsson et al (2011) compared three survey methods in a small area and estimated that the total costs of the aerial count was about 27,000 Euros, for the pellet counts it cost 8400 Euros, and for hunters' observations it cost 1600 Euros. Similarly, Rönnegård et al (2008) evaluated four methods: aerial counts, hunters' observations, pellet group counts, and cohort analysis, and they showed that the hunter's observations could be used to estimate long term trends even in moderately sized areas (~500 km²).…”
Section: Scientific Credibility and Cost Effectivenessmentioning
confidence: 99%